لعولمة المالية وأثرها على النشاط الاقتصادي لعينة من دول الشرق الأوسط (دراسة قياسية خلال فترة 1995-2019) - مسكيني, أنس; حفيظ, إلياس (جامعة الوادي - University of Eloued, 2022)
here is a wide table in the benefits and disadvantages of financial globalization, so this study came to show the impact of financial globalization on the economic activity of a sample of three countries from the Middle East (Saudi Arabia, Jordan, and Oman), and this during the period 1995-2019, and in order to reach the objectives of this study and answer the main problem, we used panel data using the fully corrected least squares method (Fmols), a method that shows us this relationship in the long term. The study found that financial globalization contributed to an increase in the average GDP per capita of the studied countries, and this is due to the fact that these countries have gradually liberalized their financial and banking systems, and this is after the application of reforms that included these systems, and financial globalization contributed to an increase in international capital flows to the countries of the study sample, which reflected positively on per capita incom
Financial globalization and its impact on the economic activity of a sample of Middle Eastern countries (Econometric study during the period 1995-2019)
مقال
Keywords: عولمة مالية ; نمو اقتصادي ; مؤشر فعلي ; مؤشر قانوني; Fmols ; Financial globalization ; economic growth ; Index Facto ; Index Jur